2016
DOI: 10.1002/psc.2891
|View full text |Cite
|
Sign up to set email alerts
|

A dimer model of human calcitonin13-32 forms an α-helical structure and robustly aggregates in 50% aqueous 2,2,2-trifluoroethanol solution

Abstract: Determining the cause of human calcitonin (hCT) aggregation could be of help in the effort to utilize hCT for treatment of hypercalcemia. Here we report that a dimer model of hCT13-32 aggregated to a greater degree than native hCT under aqueous 2,2,2-trifluoroethanol conditions. Analyses using circular dichroism spectroscopy, thioflavine-T binding assays and atomic force microscopy suggest that the α-helical portion of hCT is important for initiation of the aggregation process, which yields long fibrils. Dimer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…Notably, after reaching the maximum, the fluorescence intensity slowly declines over time. This is consistent with other reports where the decrease of the signal is likely attributed to the precipitation of hCT aggregates over the incubation period . When 5 μ m EGCG is added, there is a ≈50 % decrease in the maximum ThT fluorescence intensity compared to that of hCT only (Figure B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, after reaching the maximum, the fluorescence intensity slowly declines over time. This is consistent with other reports where the decrease of the signal is likely attributed to the precipitation of hCT aggregates over the incubation period . When 5 μ m EGCG is added, there is a ≈50 % decrease in the maximum ThT fluorescence intensity compared to that of hCT only (Figure B).…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with other reports where the decrease of the signali s likely attributed to the precipitation of hCT aggregates over the incubation period. [36][37] When 5 mm EGCG is added, there is a % 50 %d ecreasei nt he maximum ThT fluorescencei ntensity compared to that of hCT only ( Figure 1B). In the presence of 50 mm EGCG,t he maximum fluorescencei ntensity is reduced by % 80 %.…”
Section: Inhibitory Effect Of Egcg Analogues On Hct Amyloidogenesismentioning
confidence: 98%
“…Despite this variability in fibrillation, α‐helical intermediates have been observed under a range of conditions, and play a significant role in the biological function of CT ,,,,. Regarding the α‐helical intermediate, it is reported that dimerization of hCT stabilize the α‐helix under aqueous TFE solutions, leading to the long fibril formation . Within individual CT monomers, there are often multiple secondary structural motifs present that depend on the aggregation environment and could influence peptide behavior, but given the ubiquity of α‐helical intermediates, it seems generally accepted that they are a key species in the in vivo aggregation of CT ,,…”
Section: Structural Studies On Calcitonin Aggregationmentioning
confidence: 99%
“…Our result is consistent with the study of Kawashima et al . who also reported the loss of CD signal of hCT after aggregation, likely attributed to the precipitation of hCT aggregates over the course of incubation . This may also account for the decrease of ThT fluorescence intensity observed in the aggregation kinetics result (Figure A).…”
Section: Resultsmentioning
confidence: 74%